Impact of the COVID-19 pandemic and policy response on access to and utilization of reproductive, maternal, child and adolescent health services in Kenya, Uganda and Zambia. - Shiphrah Kuria-Ndiritu; Sarah Karanja; Brenda Mubita; Tonny Kapsandui; John Kutna; Dona Anyona; Joyce Murerwa; Laura Ferguson (PLOS Global Public Health)
Global health crises can negatively impact access to and utilisation of essential health services. Access to and utilisation of reproductive health services were already challenged in Sub-Saharan Africa with the COVID-19 pandemic further complicating the critical situation. This cross-sectional qualitative study aimed to assess the impact of the COVID-19 pandemic and policy responses to it on the access to, and utilization of reproductive, maternal, child and adolescent health services in Kenya, Uganda, and Zambia. It sought to explore the perspectives of women of reproductive age (18-49), frontline health workers and government representatives, all from geographies that are under-researched in this context. Using purposive sampling, key informant and in-depth interviews were carried out with 63 participants across the three countries between November 2020 and February 2021. The study population included women of reproductive age (18-49 years), front-line health service providers, and government representatives We established that COVID-19 and the policy response to it affected access to and utilization of services in the three countries, the most affected being antenatal care, delivery, family planning, and immunization services. Women reported not accessing the health facilities for various reasons. Barriers to access and utilization of services cut across all the socioecological levels. Movement restrictions, particularly in Uganda where they were most severe, and fear of contracting COVID-19 at health facilities were the most reported barriers. Weak structures at community level and inadequate supply of commodities in health facilities exacerbated the situation. Mitigation factors were put in place at different levels. There is need to strengthen the health system, particularly the supply chain and to have services closer to the community to enhance access to and utilisation of services at all times and particularly during crises such as the Covid-19 pandemic.